Pré-tratamento de casca de arroz utilizando solventes eutéticos (CLC: glicerol e CLC: ureia) e hidrólise subcrítica visando à obtenção de açúcares - Draszewski, Crisleine Perinazzo (2021)
In this research, the rice husks were submitted to pretreatments with deep eutectic solvents in order to enrich the cellulose content and reduce the lignin contents. Four mixtures of deep eutectic solvents were evaluated, Choline Chloride: Glycerol, Choline Chloride: Glycerol with water, Choline Chloride: Urea and Choline Chloride: Urea with water. At a temperature of 120 °C with a biomass/deep eutectic solvent ratio of 10, the increase in functional groups related to cellulose for pretreatments in 1, 2, 4 and 6h was evaluated using infrared spectrophotometry with Fourier transform (FT-IR). For pretreatments with the 4 mixtures of deep eutectic solvents, the best time from the FTIR was defined. The rice husks pre-treated at this time were analyzed with respect to the lignicellulosic composition by thermogravimetric analysis and the derivative of the generated thermograms (DTG). From the integration of the DTG peaks (at intervals of time defined by the literature), the levels of cellulose, hemicelluloses and lignin were determined, both in pretreated and in natura samples. The deep eutectic solvent that generated a cellulose-rich biomass was selected as the best, and the biomass from the pretreatment with it was used in the subsequent hydrolysis step. Subcritical hydrolysis was carried out in a reactor in semi-continuous operation mode. The process variables were studied: (temperature (200, 230 and 260 ° C) and mass water / solids ratio (25 and 40). The pressure was set at 15 Mpa and the total reaction time was 10 min. The highest yield of reducing sugars (49.9 ± 2.41 g / 100 g biomass) was obtained for samples of rice husks pretreated with Choline Chloride: Glycerol with water under the reaction condition in the hydrolysis step of 230 ° C / R-40. The yield was 10.21 ± 0.41 g / 100 g biomass for untreated rice husks. Rice husks pretreated with eutectic solvent showed a yield 4.9 times greater than untreated rice husks.